Involvement of an early human cytomegalovirus function in reactivation of quiescent herpes simplex virus type 2. - Colberg-Poley, A M (1981)
We have previously described an in vitro system in which the function lacking for herpes simplex virus type 2 (HSV-2) replication can be induced by human cytomegalovirus (HCMV). The mechanism of this reactivation of quiescent HSV-2 by HCMV has been further defined. The HCMV function(s) responsible for HSV-2 stimulation was examined temporally, and the fraction of cells in quiescent cultures producing HSV-2 after superinfection was determined. Using independent biological, genetic and molecular techniques we have made the following observations. (i) As early as 12 h after HCMV superinfection, HSV-2 RNA was expressed in latently infected cells. (ii) At 24 h after HCMV superinfection, a time when newly synthesized HCMV was not yet apparent, infectious HSV-2 was produced by reactivated cultures. (iii) Four HCMV temperature-sensitive mutants, which are DNA-negative at nonpermissive temperature and represent four different complementation groups, induced reactivation of HSV-2 at 39.5 degrees C. (iv) Early after HCMV superinfection, 1.6% of quiescent cells could be induced to transcribe HSV-2 information. (v) Early after HCMV superinfection, 0.3% of cells in the quiescent cultures could be induced to yield infectious HSV-2. The finding that a significant interaction can occur between HCMV and quiescent HSV-2 in an in vitro model is noteworthy in light of the knowledge that both of these herpesviruses often reside simultaneously in the human host.